Penetrating Wounds of the Heart - Fernández Perdomo, Gonzalo; Trostchansky, José; D'Auria, Agustín; Voelker, Ricardo (Cirugía del Uruguay, 1980)
Fifty two patients with cardiac wounds operated at the Hospital de Clínicas o"f Montevideo, are presented. The percentages were the same far knife and gun shot wounds. Wounds done with knife presented mainly with cardiac tamponade, while those for gun shot had frequent exanguination. Most of the patients were operated on through a left thoracotomy, and direct miocardial suture was performed.